PENGARUH TINGKAT KEPADATAN KANDANG CLOSED HOUSE TERHADAP KADAR TOTAL PROTEIN PLASMA, ALBUMIN DAN GLUKOSA DARAH AYAM BROILER STRAIN COBB - Hadi, Kemal Hazza Fadhillah; Ismoyowati, Ismoyowati; Sulistyawan, Ibnu Hari (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. The purpose of this research was to know the interaction effect of closed house stocking density on total plasma protein, albumin and blood glucose levels of cobb broiler chickens and optimal closed house stocking density for the comfort of chickens. Materials and Methods. The research was used experimental method with the stocking density treatment closed house based on harvested body weight converted (2.3 kg) into the number of chickens at the age of 21-35 days and completely randomized design (CRD), with 5 treatments and 4 replications. Treatment T1: 8 birds / m², T2: 9 birds / m², T3: 10 birds / m², T4: 11 birds / m², and T5: 12 birds / m². Result. The results of the study were the total plasma protein levels of T1 (4.05 ± 0.5); T2 (3.85 ± 0.75); T3 (4.25 ± 0.680686); T4 (3.1 ± 0.66); T5 (3.4 ± 0.54). Albumin T1 levels (4.655172 ± 0.44); T2 (4.827586 ± 0.78); T3 (3.62069 ± 0.71); T4 (3.103448 ± 0.42); T5 (3.318966 ± 0.61). Blood glucose level T1 (138.5 ± 13.30); T2 (137.5 ± 8.20); T3 (145.75 ± 13.52); T4 (113 ± 11.60); T5 (113 ± 7.16). The results of the analysis of variance showed that the closed house cage density had no significant effect (P> 0.05) on the total plasma protein content, but had a very significant effect (P <0.01) on albumin and blood glucose in broiler cobb strains. Conclusion. Based on the results of this study, the optimal level of stocking density and providing comfort based on the physiological conditions of total plasma protein, albumin and blood glucose is the stocking density level of 10 birds /m2.